An Analysis of Speech Act on Nadiem Makariem’s Speech: A Pragmatic Study - Miswaty, Titik Ceriyani; Iqbal, Muhammad (CV Insan Kreasi Media, 2023)
This research discusses Delarative sentence speech act that used by Nadiem Makariem Speech. The research aims to find out forms and functions of communication speech acts used by Nadiem Makariem in his speech. The research focused on Yule’s theory about declarative speech act. The data of this research use qualitative descriptive method. The result shows that 22 (twenty-two data). There are 21 (twenty-one) declarative speech act, 15(fifteen) form of declarative speech act, and 11 (eleven) statement found in Nadiem Makariem’s speech. So it can be concluded that the dominant form of declarative is declarative and function of communication is statement. So this speech contained declarative and statement. Declarative form is dominant in Nadiem Makarie’s speech often used statement the speaker offers it view world has they understand it.